Interventions to reduce future cancer incidence from diesel engine exhaust: What might work? - Carey, Renee; Fritschi, Lin; Driscoll, T.; Peters, S.; Glass, D.; Benke, G.; Reid, Alison (American Association for Cancer Research, 2018)
Exposure to diesel engine exhaust contributes appreciably to the burden of occupational cancer. This study aims to estimate the potential impact of a range of interventions on the future burden of cancer from occupational exposure to diesel engine exhaust in Australia. The future excess fraction method, a novel method based on the lifetime risk approach, was used to model changes in the future burden of cancer among the Australian working age population exposed to diesel engine exhaust at work in 2012 under various intervention strategies. The interventions modelled were based on the widely accepted hierarchy of control model. At baseline, 600 (0.4%) future bladder and 4,450 (0.6%) future lung cancer cases over the lifetime of the cohort were estimated to be attributable to occupational exposure to diesel engine exhaust in those exposed in 2012. Up to 2,000 of these cases were estimated to be avoidable through the use of various interventions. Exhaust hoses (engineering controls) were estimated to be particularly effective. This study provides an indication of which intervention strategies may be most useful in reducing the future burden of cancer associated with occupational diesel engine exhaust exposure. These results show the potential effect of changing current exposure, rather than focussing on past exposures, and thus provide relevant information for policy planning.